BRINGING THE REAL WORLD INTO MADRASAH CLASSROOM TEACHING INSTITUT AGAMA ISLAM NEGERI (IAIN) BENGKULU - Riswanto Riswanto (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The paper aimed at discussing the nurturing effects of utilizing second hand as authentic materials for encouraging English as a foreign language (EFL) learning atmosphere among Madrasah learners. The paper was based on the community services program conducted by writer several months ago in collaboration with research and community services unit of IAIN Bengkulu. The program involved head master, English school teacher and 90 learners of Madrasah Tsanawiyah (MTs) Mambaul Ulum at central Bengkulu district. Quasi experiment reserach design was applied to testify the hypotheses. The raw data was analyzed by SPSS software program. The findings showed that authentic media impacts significantly towards students’ motivation and learning achievement. The research result also proved that the school teachers were motivated to design their own classroom teaching media. In conclusion, the authentic materials bring the real world into the classroom teaching, promoting learners’ motivation and learning achievement. The last, encouraging teachers’ creativity in designing their own media without expense